Intravenous Thrombolysis Prior to Mechanical Thrombectomy in Acute Ischemic Stroke: Silver Bullet or Useless Bystander? - Federico Di Maria; Mikael Mazighi; Maéva Kyheng; Julien Labreuche; Georges Rodesch; Arturo Consoli; Oguzhan Coskun; Benjamin Gory; Bertrand Lapergue (Journal of Stroke, 2018)
Background and Purpose Recent single-center series and meta-analyses suggest that mechanical thrombectomy (MT) without prior intravenous thrombolysis (IVT) might be equally effective to bridging therapy. We analyzed, within the Endovascular Treatment in Ischemic Stroke (ETIS) prospective observational registry, the angiographic and clinical outcomes after IVT+MT versus MT alone. Methods From December 2012 to December 2016, a total of 1,507 consecutive patients with a proximal arterial occlusion of the anterior circulation were treated by MT. Of these, 975 (64.7%) received prior IVT. Immediate angiographic and clinical outcomes at 90 days (modified Rankin Scale [mRS]) were compared between the two groups while checking for propensity score, matched-propensity score and by inverse probability of treatment weighting (IPTW) propensity score method. Results Favorable outcome (mRS 0 to 2) was more frequently achieved after IVT+MT (n=523, 53.6%) than after MT alone (n=222, 41.8%) with an unadjusted odds ratio (OR) for bridging therapy of 1.61 (95% confidence interval [CI], 1. 29 to 2.01). This difference remained not significant in matched-propensity score cohort (OR, 1.21; 95% CI, 0.90 to 1.63) although it remained according to adjusted propensity score (OR, 1.31; 95% CI, 1.02 to 1.68) and IPTW (OR, 1.37; 95% CI, 1.09 to 1.73) analyses. A significant difference was found in terms of excellent outcome (mRS 0 to 1) (adjusted OR, 1.63; 95% CI, 1.25 to 2.11) and successful reperfusion (adjusted OR, 1.58; 95% CI, 1.33 to 2.15). No differences in intracerebral hemorrhage or in allcause mortality within 90 days were found between groups. Conclusions IVT prior to MT is associated with increased excellent outcome and successful reperfusion rates. These findings support the use of bridging therapy.